TEACHERS' ENGLISH-TEACHING STRATEGIES FOR SPECIAL NEEDS STUDENTS: A CASE STUDY AT A HOMESCHOOLING IN MEDAN - Winda Putri Sandara Butar Butar; Emeliya Sukma Dara Damanik (FRASA: ENGLISH EDUCATION AND LITERATURE JOURNAL, 2025)
Students with special needs often face challenges in learning English effectively, highlighting the importance of teachers’ strategies in supporting their educational success. This study aimed to explore the strategies used by teachers in teaching English to students with special needs at Cadika Homeschooling (a pseudonym). Employing a qualitative case study design, data were collected from three English teachers (two females and one male) through criterion sampling. The instruments used included direct classroom observations, documentation of therapists’ psychological notes, and interviews conducted via WhatsApp voice recordings. Data were analysed thematically. The findings revealed that teachers implemented various strategies for students with Autism Spectrum Disorder (ASD), such as multimedia visual strategies and the use of images, videos, and colour-based materials. Additionally, they adopted structured learning approaches involving digital aids and role-play activities. For slow learners, teachers applied direct practice methods through engaging activities and relationship-building approaches to foster motivation and confidence. These strategies enabled teachers to create a comfortable and emotionally supportive learning environment, facilitating better language acquisition. The study recommends that teachers integrate adaptive media, structured approaches, and relationship-focused methods to enhance the learning experiences and outcomes of students with special needs.